Про один підхід до обробки великих обсягів неструктурованих даних - Полурєзов, Д. С. (ХНУРЕ, 2024)
The issue of real-time processing of large datasets is delineated. The utilization of binary search method for handling unstructured data through parallelizing queries to remote repositories according to the number of processor cores of the mobile device is examined. This method can find its application in organizing parallel processing of substantial volumes of unstructured information on personal mobile devices operating under the iOS operating system.
Keywords: неструктуровані дані; Big Data